QUALITY OF A COHESIVE SOIL UNDER CONSERVATION PRACTICES: A GEOSTATISTIC APPROACH - Francisco Ivo dos Santos Aguiar; Ismênia Ribeiro de Oliveira; Klayton Antonio do Lago Lopes; Jussara Silva Dantas; James Ribeiro de Azevedo (Colloquium Agrariae, 2023)
The knowledge and characterization of aggregate stability are relevant to select adequate management and to avoid its degradation. Thus, this work aimed to characterize the spatial variability of aggregate stability in cohesive soils under crop conservation systems. The experiment was performedin two different areas of soybean production: no-tillage System (NTS) and livestock farming integration system (LFI), In each production area, a sampling mesh composed of 50 collection points, with a regular spacing of 40 m, at 0.00-0.20 m depth, was carried out. The results were expressed as a percentage of aggregates retained in sieves 2; 1; 0.5 and 0.25 mm, the values obtained were used to calculate the Mean Geometric Diameter (MGD) and Mean Weight Diameter (MWD). In the LFI system, which had a strong degree of spatial dependence (DSD), the attributes showed a moderate DSD, except for MWD. Generally, the reached values of the attributes in the LFI system were lower than those found in the NTS system, showing less variability in the management system with no-tillage. Spatial distribution of the kriging maps demonstrated the LFI system leading to the formation of larger aggregates in the soil when compared to ones to the same attributes in the NTS. All attributes showed a strong to moderate spatial dependence. The soil managed with the LFI system revealed greater aggregate stability when compared to the NTS, which in turn presented less spatial variability than the LFI system and shows a more homogeneous soil.